Pengaruh Biblioterapi Menggunakan Longer Picture Book Terhadap Tingkat Kecemasan Anak Usia 3-6 Tahun Pada Masa Hospitalisasi - Fakultas Keperawatan DELI HUSADA Deli Tua (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Children are part of family and society. Children assume hospitalization is a threatening condition for him so that the response that arises is anxiety. Anxiety in chlidren is characterized by children refusing to eat and drink, difficulty sleeping, crying continuously, not cooperating with health workers. To reduce his anxiety, he can use the book as a therapeutic media called bibliotherapy. his study aims to determine the effect of bibliotherapy using longer picture books on anxiety levels of children aged 3-6 years during hospitalization. The type of research was pre-experimental with the design of one group pretest - posttest desaign without the control group with 31 respondents. The sampling technique is Consecutive sampling. The data collection tool uses observation. The results showed that the average anxiety level before bibliotherapy used a longer picture book, which was 39.16, while after bibliotherapy it used a longer picture book which was 23.71. With the Wilcoxon test obtained p-value = 0,000 <ɑ (0.05), then H₀ is rejected, meaning there is a significant influence between bibliotherapy using longer picture book on anxiety levels of children aged 3-6 years during hospitalization at Sembiring General Hospital. It is expected that parents can continue to teach children to read so that children's reading comprehends and can take lessons from the story